Media Sosial Instagram sebagai Media Promosi Daya Tarik Wisata di Kabupaten Pulau Morotai - Hito, Giska; Ihalauw, John Joi; Damiasih, D (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to describe the promotional strategy carried out by the Morotai Island Regency Tourism Office via Instagram social media. Interviews with the marketing division of the Morotai Island Regency Tourism Office and followers of the @dispar.morotai account were research subjects using qualitative descriptive methods. The data obtained was primary and secondary data, through observation, interviews and documentation. The research results show that the Morotai Island Regency Tourism Office has not maximized the use of Instagram social media to promote tourist attractions. This promotional strategy involves several stages, such as segmentation, targeting, positioning, and branding.